Pengaruh Kepuasan Kerja, Komitmen Organisasi Dan Lingkungan Kerja Terhadap OCB (Organizational Citizenship Behaviors) (Studi Kasus Karyawan Koperasi Sadar Sejahtera Sumatera Selatan) - Deniyati Zufriah (Relevance: Journal of Management and Business, 2019)
Technological developments in the era of globalization are increasingly fast demanding every company to develop strategies and management policies, especially in the field of human resources (HR), other factors that influence the work environment, and organizational commitment, where the better both can create job satisfaction in employees can even indirectly form organizational citizenship behavior. The purpose of this study was to examine and analyze the effect of job satisfaction, organizational commitment and work environment on organizational citizenship behavior (OCB) employees of Sadar Sejahtera Cooperative, South Sumatra. This study uses a quantitative approach. The study was conducted at the Sadar Sejahtera Cooperative in September 2019. The population in this study was 145 respondents while the sample used was 100 respondents. The sampling method uses nonprobability sampling and the sampling technique uses purposive sampling. The data analysis technique used in the study is multiple linear regression test. The analysis showed that partially job satisfaction (p value = 0.001); organizational commitment (p value 0.001) and work environment (p value = 0.025) affect Organizational citizenship behavior. Furthermore, simultaneous job satisfaction, organizational commitment and work environment influences organizational citizenship behavior (OCB) employees of Koperasi Sadar Sejahtera, South Sumatra with a calculated F value of 0,000.